Analysis of QoS in 4G LTE Networks During Handover Process - Yayan Amrullah; Abdullah Zainuddin; Sudi Mariyanto AI Sasongko (International Journal of Informatics and Computation, 2025)
This study analyzed Quality of Service (QoS) in 4G LTE networks during the handover process, focusing on the parameters RSSI, RSRQ, SINR, and throughput. We conducted data collection through a drive test using the G-NetTrack Pro application in the morning, afternoon, and evening. The measurement results showed a Handover Success Rate (HOSR) of 96.6%, slightly below Telkomsel’s mobility KPI target (>98%). The majority of RSSI and SINR values were in the good to very good category, although there were cases of significant signal quality degradation after handover with a throughput reduction of up to 1.28 Mbps. Factors causing the decline in performance included high user density in the destination cell (BTS 2), interference, and physical environmental conditions such as buildings and trees. This study displayed the importance of considering signal quality parameters (RSRQ and SINR) in addition to signal strength (RSRP) in cell selection logic to improve handover success.